Creation of Ready-to-Wear Deluxe Clothes Source of Philosophy and Form of Tikel Balung Traditional Houses with the Concept of Transformation - Colodia, Sindi; Arifiana, Deny; Hidayati, Lutfiyah; Mayasari, Peppy (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This research is creation research that raises local cultural values ​​as an alternative innovation amidst the dominance of Western styles in the fashion industry. The Tikel Balung traditional house is a cultural heritage of the Osing tribe that is still preserved today. The shape and philosophy of the house are a source of inspiration in creating a ready-to-wear deluxe with a transformation concept. This research uses the practice-led research creation method with the aim of 1) describing the creative process of compiling sources of ideas. 2) describing the process of creating collections, 3) describing the finished results. 4) describing the presentation of the collections. The results of this study include: 1) the creative process of compiling sources of ideas that are manifested in a mood board, 2) describing the process of creating collections based on the practice-led research method, starting from pre-design, design, manifestation, to presentation of works, 3) describing the finished results of three collections, consisting of two women's clothes and one men's clothes with a transformation concept, and 4) presenting collection in three activities: pre-event, event, and post-event.